Augmenting Instructional Animations with a Body Analogy to Help Children Learn about Physical Systems - Pouw, Wim T. J. L.; van Gog, Tamara; Zwaan, Rolf A.; Paas, Fred (Frontiers in Psychology, 2016)
We investigated whether augmenting instructional animations with a body analogy would improve 10-13 year old children’s learning about class-1 levers. Children with a lower level of general math skill who learned with an instructional animation that provided a body analogy of the physical system, showed higher accuracy on a lever problem-solving reaction time task than children studying the instructional animation without this body analogy. Additionally, learning with a body analogy led to a higher speed-accuracy trade-off during the transfer task for children with a lower math skill, which provided additional evidence that especially this group is likely to be affected by learning with a body analogy. However, overall accuracy and solving speed on the transfer task was not affected by learning with or without this body analogy. These results suggest that providing children with a body analogy during animation study provides a stepping-stone for understanding mechanical principles of a physical system, which may prove useful for instructional designers. Yet, because the body analogy does not seem effective for all children, nor for all tasks, the degree of effectiveness of body analogies should be studied further. Future research, we conclude, should be more sensitive to the necessary degree of analogous mapping between the body and physical systems, and whether this mapping is effective for reasoning about more complex instantiations of such physical systems.